Analytical Method of Profiling Axial-Radial Compressor Impellers - Rusanov, A.V.; Rusanov, R.A.; Pashchenko, N.V.; Chuhai, M.O. (Проблеми машинобудування, 2018)
A new analytical method for constructing axial-radial compressor impellers with compound lean leading and trailing edges is proposed allowing us to describe a wide class of flow paths based on a limited (small) number of parameterized quantities. With the aid of this method there has been designed a new flow path with a typical axial radial impeller for turbo-expander aggregate compressors with flow coefficients in the range from 0.03 to 0.06. To test the method, a numerical study of spatial viscous flows was carried out in the existing and new modifications of the flow path for the typical axial-radial compressor of a low-temperature turbo-expander aggregate. To do that, the IPMFlow software package was used, which is the development of the FlowER and FlowER-U programs.